2020
DOI: 10.3390/jcm9072313
|View full text |Cite
|
Sign up to set email alerts
|

Accuracy of Panoramic Radiograph for Diagnosing Periodontitis Comparing to Clinical Examination

Abstract: In this study, we explore the diagnostic accuracy of a Radiographic-based Periodontal Bone Loss (R-PBL) method as a screening tool for periodontitis, in the form of radiographic bone loss, under the 2018 case definition in comparison to the 2012 case definition. The analysis was based on 456 patients (253 females and 203 males), screened for periodontal status in the Study of Periodontal Health in Almada-Seixal (SoPHiAS) project and subjected to a panoramic dental X-ray. Patients were diagnosed for the presenc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
22
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(23 citation statements)
references
References 34 publications
1
22
0
Order By: Relevance
“…Since it visualizes the entire area in a single film, including maxilla, mandible, and temporomandibular joints, it is useful for treatment planning of extractions, implants, and dentures. Also, it is a reliable tool in observation of alveolar bone loss caused by periodontal disease; however, this method is not suitable to diagnose the activity of periodontal disease since it hardly provides information about periodontal soft tissues [83]. Intraoral X-rays take an image with a radiographic film or a detector placed inside the mouth and are used in periapical views to provide precise and detailed information about each tooth and partial bone with various views.…”
Section: -Dimensional Imaging With Radiographymentioning
confidence: 99%
“…Since it visualizes the entire area in a single film, including maxilla, mandible, and temporomandibular joints, it is useful for treatment planning of extractions, implants, and dentures. Also, it is a reliable tool in observation of alveolar bone loss caused by periodontal disease; however, this method is not suitable to diagnose the activity of periodontal disease since it hardly provides information about periodontal soft tissues [83]. Intraoral X-rays take an image with a radiographic film or a detector placed inside the mouth and are used in periapical views to provide precise and detailed information about each tooth and partial bone with various views.…”
Section: -Dimensional Imaging With Radiographymentioning
confidence: 99%
“…However, Machado et al (2020) highlighted limitations of radiographic assessment, such as the inability to reproduce the bone structure three-dimensionally, which may decrease accuracy. Also, lack of standardization in radiography may show milder bone destruction than observed ( Vijay and Raghavan, 2013 ).…”
Section: Discussionmentioning
confidence: 99%
“…Although intraoral radiographs may be less accurate than other techniques, recent studies focus on computer-assisted radiography to overcome human visual limitations in detecting bone loss. Recent studies suggested that automated systems could allow more reliable and accurate assessments of periodontal bone loss on panoramic dental radiographs, and the development of automated prediction systems could enhance periodontitis surveillance ( Krois et al, 2019 , Machado et al, 2020 ).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations